2021
DOI: 10.3389/fnagi.2021.698036
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic System in the Central Nervous System, a Novel Therapeutic Direction Against Brain Edema After Stroke

Abstract: Stroke is the destruction of brain function and structure, and is caused by either cerebrovascular obstruction or rupture. It is a disease associated with high mortality and disability worldwide. Brain edema after stroke is an important factor affecting neurologic function recovery. The glymphatic system is a recently discovered cerebrospinal fluid (CSF) transport system. Through the perivascular space and aquaporin 4 (AQP4) on astrocytes, it promotes the exchange of CSF and interstitial fluid (ISF), clears br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 142 publications
(202 reference statements)
0
19
0
Order By: Relevance
“…44,46 At this stage, the ventricles may dilate due to disruption of the CSF circulation caused by a damaged nerve system. 47 Alternatively, the CSF pressure in the ventricular structures may decrease to increase the clearance of edema, resulting in ventricle enlargement. 48 As in previous studies, our further study confirmed the effect of edema on ventricular volume through changes in ADC and edema volume (Supplementary Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…44,46 At this stage, the ventricles may dilate due to disruption of the CSF circulation caused by a damaged nerve system. 47 Alternatively, the CSF pressure in the ventricular structures may decrease to increase the clearance of edema, resulting in ventricle enlargement. 48 As in previous studies, our further study confirmed the effect of edema on ventricular volume through changes in ADC and edema volume (Supplementary Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Glymphatic and meningeal lymphatic dysfunction of the brain has been observed in patients with ischemic stroke [169][170][171]. This abnormality may promote the formation of brain edema in some neurological disorders, including ischemic stroke and subarachnoid hemorrhage.…”
Section: Brain Lymphatic Drainagementioning
confidence: 99%
“…In addition to an altered barrier function between blood and the brain’s parenchyma, the influx of cerebrospinal fluid was recognized as a significant factor for edema formation in stroke [ 13 , 14 ]. Further, the glymphatic system, representing a unique cleaning pathway that uses perivascular spaces to flush the brain’s interstitium was recently discussed to be involved in ischemia-associated edema formation [ 15 , 16 , 17 ]. In this context, a pivotal role in blood-brain barrier functionality and brain fluid homeostasis has been attributed to the aquaporin-4 (AQP4) water channel, which is typically located at the astroglial end-feet [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%